Functional System of Creative Thinking - Kotsan, Ihor Ya.; Kozachuk, Nataliia O.; Kachynska, Tetiana V.; Shvarts, Liudmyla O.; Poruchynskyi, Andrii I.; Dmytrotsa, Olena R.; Abramchuk, Olha M.; Zhuravlov, Oleksandr A.; Poruchynska, Tetiana F.; Коцан, Ігор Ярославович; Козачук, Наталія Олександрівна; Качинська, Тетяна Володимирівна; et al. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2016)
In the article on the basis of electroencephalographic and psychological indicators the concept the mechanism of creative thinking was formulated. Creative thinking as a process involves operating images and searching similar tasks in memory (mental representations). High result in creative thinking is possible under the condition of high decision-making and low level of critical-controlling program.
Keywords: creative thinking; beta-rhythm; alpha-2-rhythm; delta-rhythm; electrical activity of the cerebral cortex